Nuclear localization of factor inhibitor hypoxia-inducible factor in prostate cancer is associated with poor prognosis. - Shaida, N; Chan, P; Turley, H; Jones, C; Kanga, S; Ritchie, R; Malone, P; Harris, A; Fox, S (2011)
PURPOSE: We determined the role of factor inhibiting hypoxia-inducible factor-1 in prostate cancer specimens. MATERIALS AND METHODS: A tissue microarray of 152 prostate cancers was constructed and stained for factor inhibiting hypoxia-inducible factor-1, hypoxia-inducible factor-1α and 2α, and glucose transporter 1 as a prototypical downstream target of hypoxia-inducible factor-1α. Correlation analysis was done between these variables, and between factor inhibiting hypoxia-inducible factor-1, and clinical and pathological variables, including prostate specific antigen as a surrogate of recurrence. RESULTS: Factor inhibiting hypoxia-inducible factor-1 was expressed in the cytoplasm and/or the nucleus in 86.5% of tumors, including exclusive cytoplasmic expression in 51.3% and exclusive nuclear expression in 5.3%. Any nuclear and exclusive expression of factor inhibiting hypoxia-inducible factor was associated with poor prognosis on univariate analysis (p = 0.007 and 0.042, respectively). On multivariate analysis men with nuclear expression in tumors were twice as likely to experience recurrence (p = 0.034). CONCLUSIONS: Factor inhibiting hypoxia-inducible factor-1 is widely expressed in prostate tumors. Its differential subcellular expression suggests that regulation of its expression is an important factor in the activity of the hypoxia-inducible factor pathway. Its modulation may help treat hypoxia-inducible factor driven aggressive prostate cancer.